GOVERNANCE ISSUES IN MALAYSIA’S LIMITED LIABILITY PARTNERSHIPS (LLP) - Ghadas, Zuhairah Ariff Abd; Rahman, Hamizah Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Limited liability partnerships (LLP) are a new hybrid business vehicle in Malaysia that are governed under the Limited Liability Partnerships Act 2012. The main uniqueness of LLPs is that they can be set up not only by business partners, but any two or more individuals - from family members, professionals, and other legal entity such as the Federal Teritory of Labuan or even the Football Association of Malaysia (FAM). This paper dliberates the corporate governance models from the other countries that are pertinent to the current practices for LLPs. In comparison with other countries such as United Kingdom, India and Singapore, the Malaysian LLP has similar attributes as a body corporate, offering internal flexibility similar to a partnership, but regulated by the members’ or partnership agreement. Despite being a body corporate, LLPs face the inappropriteness of direct applications of corporate governance principles, as profound systems to control and manage LLPs within the accontability of its partners and stakeholders. Thus, this paper highlights the major governance issues for the LLPs in Malaysia: inclusive jurisdictions or legal issues and other aspects.